Pembangkitan Data Debit dan Skenario Pola Tanam Daerah Irigasi Embung Suruhan - Pratiwi, Bertha Silvia; Sachro, Sri Sangkawati; Suharyanto, Suharyanto (Department of Civil Engineering, Diponegoro University, 2017)
The availability of historical data used in hydrological analysis is often incomplete and very short, so the information obtained from the data is also very little. If continue to use incomplete historical data or a little period of time, the analysis results will not match the circumstances in the field. Hydrology analysis in planning of Embung Suruhan uses rainfall data from Jiken Station, Blora Station and Bogorejo Station from 1986-2006 and climatology data of Tempuran Reservoir Station 1986-2005 with 4.6 million m3. The next study, capacity 6.69 million m3 with rainfall data from five stations, namely: Blora station, Jiken, Gayam, Greneng, and Tempuran from 1997-2012 and climatological data of Tempuran Reservoir and Kedung Ombo Reservoir. This research is to get the requirement of optimal irrigation with forecasting of discharge data and simulation of initial variation of planting and some scenario type of planting pattern from Embung Suruhan. Discharge was analyzed by Mock method and then raised up to 25 years with Thomas Fiering model and to get the water availability used Basic Year. The discharge data has characteristics that are close to historical data and in 2018 as the basic year used for water availability.